Characteristics of Hunter Harvested Montezuma Quail Wings and Implications for Molt Phenology - Charles J Randel III; Pedro M. Chavarria; C. Zach Johnson; Roel R. Lopez; John M. Tomeček; Nova J. Silvy (National Quail Symposium Proceedings, 2022)
We obtained 1,899 hunter-harvested Montezuma quail (Cyrtonyx montezumae) wings from southeastern Arizona, USA, from the 2008–2009 hunting season. We determined age and sex based on plumage characteristics for 98.2% (1,864) of the original sample. One-way analysis of variance (ANOVA) of wing-chord length found differences (P < 0.001) based on sex, but not age, with mean (± standard error) male wing chord (113.76 ± 0.15 mm) longer than mean female wing chord (111.03 ± 0.13 mm). Mean male and female wing-chord lengths from our study population were 6.8% and 7.7% shorter, respectively, than previously reported in the literature. We additionally calculated a complete prebasic molt cycle of 177 days based on previously reported preformative molt patterns. The primary benefits of our results are: 1) a more accurate sex-based wing-chord length based on a large sample size, 2) a method to back-calculate molt onset dates for hunter harvested after hatch year Montezuma quail, and 3) a potential means to model the influence of precipitation on population dynamics of Montezuma quail.
Keywords: Arizona; Cyrtonyx montezumae; Montezuma quail; molt phenology; wing chord